2018
DOI: 10.1093/jxb/ery129
|View full text |Cite
|
Sign up to set email alerts
|

Shade compromises the photosynthetic efficiency of NADP-ME less than that of PEP-CK and NAD-ME C4 grasses

Abstract: Photosynthesis and productivity are less compromised by low light in NADP-ME C4 grasses relative to PEP-CK and NAD-ME counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
67
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 79 publications
8
67
1
Order By: Relevance
“…Oxidoreductase activity is often linked with the cyclic electron flow (CEF) around photosystem I (Takabayashi et al , ), and NADP‐ME species have been reported to utilize the highest amount of CEF (Hernández‐Prieto et al , ). Plasticity within CEF could have implications in the ability to acclimate to low light, and the subtype‐specific nature of this plasticity could have implications in the lower susceptibility of NADP‐ME species to shade that has previously been reported (Sonawane et al , ). Within NAD‐ME species an increased enrichment in categories related to starvation was noted within the downregulated DE transcripts.…”
Section: Discussionmentioning
confidence: 90%
“…Oxidoreductase activity is often linked with the cyclic electron flow (CEF) around photosystem I (Takabayashi et al , ), and NADP‐ME species have been reported to utilize the highest amount of CEF (Hernández‐Prieto et al , ). Plasticity within CEF could have implications in the ability to acclimate to low light, and the subtype‐specific nature of this plasticity could have implications in the lower susceptibility of NADP‐ME species to shade that has previously been reported (Sonawane et al , ). Within NAD‐ME species an increased enrichment in categories related to starvation was noted within the downregulated DE transcripts.…”
Section: Discussionmentioning
confidence: 90%
“…NADP-ME genes can be classified into photosynthetic and non-photosynthetic types. The former mostly function in the chloroplasts [13] and improve photosynthetic efficiency by facilitating the release of CO 2 from decarboxylation of malate in proximal bundle-sheath cells, and in C 4 plants by providing CO 2 to Rubisco for carbon fixation [14,15]. Genomic and phylogenetic analyses showed that the NADP-ME gene family in the Poaceae has four branches, with one branch (NADP-ME IV) being expressed in the plastids.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in most field situations where C 4 crops and grasses form thick canopies, a substantial proportion of the vegetative part of the plant may experience shade or natural low light. Under such unfavourable conditions, C 4 leaves can undergo both biochemical and anatomical changes as part of their acclimatory response (Pengelly et al, ; Sonawane, Sharwood, Whitney, & Ghannoum, ; Tazoe, Hanba, Furumoto, Noguchi, & Terashima, ; Tazoe, Noguchi, & Terashima, ). Responses of C 4 plants, however, appear to differ depending on the decarboxylation subtype (NADP‐ME, NAD‐ME, or PCK; Sonawane et al, ), whether the plants are monocots or dicots (Pengelly et al, ; Sonawane et al, ; Tazoe et al, ; Tazoe et al, ), or even between species (Ward & Woolhouse, ).…”
Section: Introductionmentioning
confidence: 99%